2008
DOI: 10.1038/nmat2119
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-dependent ionization energies and interface dipoles in ordered molecular assemblies

Abstract: S. Duhm et al., Nature Materials, acceptedWhile an isolated individual molecule clearly has only one ionization potential, multiple values are found for molecules in ordered assemblies. Photoelectron spectroscopy of archetypical π-conjugated organic compounds on metal substrates combined with first-principles calculations and electrostatic modeling reveal the existence of a surface dipole built into molecular layers. Conceptually different from the surface dipole at metal surfaces, its origin lies in details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
592
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(639 citation statements)
references
References 49 publications
45
592
2
Order By: Relevance
“…Its lack of a photon-energy dependence of E final (∆ 0) identifies it as a discrete final state located above the global vacuum level, as was also reported e.g. for the unoccupied π* e 2u state of benzene on Cu(111) [12].…”
Section: Interface Coupling and Thesupporting
confidence: 56%
See 1 more Smart Citation
“…Its lack of a photon-energy dependence of E final (∆ 0) identifies it as a discrete final state located above the global vacuum level, as was also reported e.g. for the unoccupied π* e 2u state of benzene on Cu(111) [12].…”
Section: Interface Coupling and Thesupporting
confidence: 56%
“…Structure is often inferred spectroscopically [11][12][13], an approach that works well for highly ordered organic thin films such as e.g. C 60 on Cu (111) [14] or PTCDA on Ag (111) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the work function of organic semiconductor molecules chemisorbed on metals is closely correlated to the orientation of the chemisorbed molecules. 34 In view of the relatively high work function of TCNQ/Fe interface (~5.5 eV) in present studies, it is believed that the molecular plane of adsorbed TCNQ is parallel to Fe substrate, i.e., TNCQ molecules "lay" on the substrate in the interface formation. However, as TCNQ deposition goes on, the work function decreases, by about 0.2 eV.…”
Section: Experimental Methodsmentioning
confidence: 62%
“…A change in the static environment can change the ionization potential considerably, as is demonstrated convincingly on molecular layers with different orientations [25]. The pinning level would be affected in a similar way.…”
Section: (D)-(i)mentioning
confidence: 67%